Tailoring mSiO2-SmCox nanoplatforms for magnetic/photothermal effect-induced hyperthermia therapy - Liang, Xinqiang; Xu, Wenting; Li, Siyi; Kurboniyon, Mekhrdod S.; Huang, Kunying; Xu, Guilan; Wei, Wene; Ning, Shufang; Zhang, Litu; Wang, Chen (Frontiers in Bioengineering and Biotechnology, 2023)
Hyperthermia therapy is a hotspot because of its minimally invasive treatment process and strong targeting effect. Herein, a synergistic magnetic and photothermal therapeutic nanoplatform is rationally constructed. The well-dispersive mSiO2-SmCox nanoparticles (NPs) were synthesized through a one-step procedure with the regulated theoretical molar ratio of Sm/Co among 1:1, 1:2, and 1:4 for controlling the dispersion and magnetism properties of SmCox NPs in-situ growth in the pore structure of mesoporous SiO2 (mSiO2), where mSiO2 with diverse porous structures and high specific surface areas serving for locating the permanent magnetic SmCox NPs. The mSiO2-SmCox (Sm/Co = 1:2) NPs with highly dispersed and uniform morphology has an average diameter of ~73.08 nm. The photothermal conversion efficiency of mSiO2-SmCox (Sm/Co = 1:2) NPs was determined to be nearly 41%. The further in vitro and in vivo anti-tumor evaluation of mSiO2-SmCox (Sm/Co = 1:2) NPs present promising potentials for hyperthermia-induced tumor therapy due to magnetic and photothermal effects.